Don't let the tail(ings) wag the mine: guiding tailings storage facility closure designs for compliance - Walls, J (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Navigating the choppy waters of tailings storage facility (TSF) closure is no simple feat — it’s a bit like teaching an old dog new tricks, but with more environmental regulations. TSFs can be some of the most complex mine closure components, as they pose significant environmental, social and economic risks if not properly designed, constructed and rehabilitated. The Global Industry Standard on Tailings Management (GISTM) provides a framework for the safe management of TSFs throughout their lifecycle, from planning to closure and post-closure. This paper presents some of the lessons learnt and challenges encountered while undertaking engineering closure designs of TSFs for GISTM compliance, with a focus on aligning with the United Nations Sustainable Development Goals (UN SDGs). The paper discusses the closure hierarchy that is typically considered for TSFs, which serves as a foundational framework for identifying appropriate post-closure land uses and for developing robust engineering designs. It suggests that it is possible to design and implement closure strategies for TSFs that not only meet GISTM standards but also contribute to achieving several UN SDGs. Additionally, the paper examines strategies to reduce both initial investment and ongoing costs associated with monitoring and maintenance post-closure. Some of the challenges that are highlighted in the paper include the knowledge base, uncertainties regarding the long-term performance and behaviour of TSFs, and the design life of the closure components. By sharing insights and experiences from TSF closure design projects, which sometimes feels like trying to tame a beast before it hibernates, this paper aims to provide some recommendations and best practices for future projects.
Keywords: closure designs